2021
DOI: 10.1186/s12877-021-02115-y
|View full text |Cite
|
Sign up to set email alerts
|

The psychometric evaluation of the sense of belonging instrument (SOBI) with Iranian older adults

Abstract: Background A sense of belonging is a significant predictor of mental health and well-being in later life. A sense of belonging in childhood and adolescence contributes to a number of adult behavioural and psychological outcomes. A high sense of belonging has been associated with better health, longevity, psychological well-being, and disease recovery. Methods In this study, the Persian version of the Sense of Belonging Instrument (SOBI) for older a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…The need to belong has been generally defined as a pervasive desire to form and maintain interpersonal connections [62,63]. The fulfillment of the need to belong is associated with a broad range of positive emotions and overall well-being [64,65]. Failure to maintain social relationships results in unfulfilled belonging needs and consequently a wide array of adverse psychological, physical, and pathological outcomes [66,67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The need to belong has been generally defined as a pervasive desire to form and maintain interpersonal connections [62,63]. The fulfillment of the need to belong is associated with a broad range of positive emotions and overall well-being [64,65]. Failure to maintain social relationships results in unfulfilled belonging needs and consequently a wide array of adverse psychological, physical, and pathological outcomes [66,67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Older adults were identified as at higher risk as they are more likely to have pre-existing conditions including heart disease, diabetes, and severe respiratory conditions [ 5 ]. Additionally, recent research highlights that COVID-19 and its safety measures led to increased mental health problems, including increased feelings of depression, anxiety, social isolation, and loneliness, potentially cognitive decline [ 6 22 ]. Other studies reported the consequences of only age-based protective health measures including self-isolation for people older people (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have stressed that this combination, leading to a greater physical vulnerability, created a psychosocial threat from SARS-CoV-2 [5][6][7]. For some people, the COVID-19 health and safety measures led to increased mental health problems, such as increased anxiety, feelings of depression, social isolation, and loneliness [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%